BUDAYA DI SMA N 10 PALEMBANG YANG MENCERMINKAN NILAI-NILAI PANCASILA DAN KEBHINEKATUNGGALIKAAN SEBAGAI UPAYA PEMBENTUKAN KARAKTER PELAJAR PANCASILA - NURHALIMAH (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2023)
School is the main target in the formation of the character of students. SMA N 10 Palembang implements the values of Pancasila and diversity through school culture as an effort to shape the character of Pancasila students. Forms of culture that exist in SMA N 10 Palembang such as reading prayers before starting learning, Duha prayers together, 5S habituation, election of student council presidents, group discussions, and waste bank activities. Based on the results of observations and literature studies conducted, the culture in SMA N 10 Palembang already reflects the values of Pancasila and diversity to shape the character of Pancasila students who are faithful, devoted to God Almighty, have noble character, have global diversity, are independent, work together, think critically and creatively.